Density of jatropha curcas seed oil and its methyl esters: measurement and estimations - Veny, H.; Baroutian, S.; Aroua, M.K.; Hasan, M.; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (2009)
Density data as a function of temperature have been measured for Jatropha curcas seed oil, as well as biodiesel jatropha methyl esters at temperatures from above their melting points to 90 (A degrees) C. The data obtained were used to validate the method proposed by Spencer and Danner using a modified Rackett equation. The experimental and estimated density values using the modified Rackett equation gave almost identical values with average absolute percent deviations less than 0.03 for the jatropha oil and 0.04 for the jatropha methyl esters. The Janarthanan empirical equation was also employed to predict jatropha biodiesel densities. This equation performed equally well with average absolute percent deviations within 0.05. Two simple linear equations for densities of jatropha oil and its methyl esters are also proposed in this study.